Innate and adaptive immune patterns in hospitalised COVID-19 patients: a framework for precision monitoring in viral and inflammatory syndromes - Corrao, Salvatore; Bocchio, Raffaella Mallaci; Scibetta, Salvatore; Montalbano, Antonella; Natoli, Giuseppe; Calvo, Luigi; Gervasi, Francesco; Argano, Christiano; , Internal Medicine IGR COVID-19 Investigators (Frontiers in Immunology, 2026)
BackgroundUnderstanding immune responses in viral infections such as COVID-19 is crucial for identifying patients at risk of clinical deterioration. Profiling innate and adaptive immune components may provide a basis for precision monitoring and personalised management strategies in infectious and inflammatory syndromes.MethodsIn a prospective observational study, 150 patients were enrolled from 30 March to 15 April 2022, hospitalised for COVID-19 at a tertiary Internal Medicine COVID Unit. Flow cytometry analysis of peripheral blood quantified 34 immune subpopulations. Patients were stratified into immunophenotypic groups based on deficiencies in T helper (CD4), cytotoxic T (CD8), natural killer (NK), and plasma cells. Clinical outcomes were analysed in relation to these immune profiles using multivariate logistic regression.ResultsOf the 150 patients (mean age 64.7 years, 59.1% male), 7.8% required ICU admission and 9.1% died. Lymphopenia (<1200 cells/µL) was observed in 84%, with 61.1% showing CD4+ T cell deficiency, 32.2% NK cell deficiency, 46% CD8+ T cell reduction, and 26.6% decreased plasma cells. Notably, 10% had concurrent CD4 and NK cell deficiencies. While low plasma cell counts were not associated with worse outcomes, NK cell deficiency was linked to a threefold increased risk of death or ICU transfer (OR 3.19, p<0.03), and CD4+ T cell reduction was associated with a 5.23-fold increase (p<0.037). The combination of low CD4 and NK cells resulted in a 9.5-fold higher risk of adverse outcome, independently of age and sex.ConclusionsSpecific immune profiles, particularly reductions in CD4+ and NK cells, are strong predictors of mortality or ICU admission in hospitalized COVID-19 patients. These findings suggest that rapid and clinically feasible tool may support precision monitoring and personalised management in viral and inflammatory syndromes beyond COVID-19. This study advocates for the integration of immune profiling into the framework of precision medicine.